DESIGN OF ENERGY MANAGEMENT SYSTEMS FOR MICROGRIDS (Global Journal of Advanced Engineering Technologies and Sciences, 2022)
Microgrids are low-voltage, reliable, economic, renewable energy resources that help to reduce the increasing demand of energy. Microgrids are environmentally friendly because of their renewable energy resources. The installations of various renewable energy resources are increasing day by day to produce vast amounts of energy. The management of produced energy is operated by a central software system, called Energy Management System (EMS). According to our literature review of microgrid EMSs, we notice that the capabilities of traditional EMSs are limited, and these are tightly coupled with the EMSs. This is considered as an obstacle for sustainable development of microgrid EMSs. We need EMSs whose capabilities have to be flexible, reusable, and interoperable against the traditional EMSs that ensure the sustainability of EMSs. Based on our literature review, we find that the Service Oriented Computing (SOC) is a computing paradigm that helps to develop a flexible, reusable, and interoperable EMS. In this thesis, we propose to design EMS based on the design principles of SOC. We design five categories of REST ful Web services to develop service-oriented EMSs for microgrids. By using these REST full Web services, a sustainable microgrid EMS can be developed. We design and implement a small service-oriented microgrid EMS by using our designed Web services that simulate distributed energy resources (wind turbine, photovoltaic) and distributed energy storage (battery). We use real energy consumption data with the simulated data to make the system operational